Perbandingan Metode Tabu Search dengan Metode Hungarian Algorithm untuk Penentuan Driver Assignment pada Simulasi Taksi Online - Eryn Eryn; Andreas Handojo; Tanti Octavia (Jurnal Infra, 2020)
Taxi in one of the public transportation that is widely used by people in all parts of the world. Over time, taxis have continued to grow until now online taxis have emerged. Taxis also develop in the dispatch function in installing drivers with requests from customers. As the function of installing drivers to this request develops, the parameters used to get matching results also increase and the complexity increases. However, with the conditions that are increasingly developing, the matching process between drivers and customers is still required to use the least amount of time and resources and still produce optimal results. So from this, in this matching process a lot of progress was made in order to get the results of installing drivers to customers that can minimize time and distance.The application is made in Python programming language, Bootstrap 3 for the front end menu, and django as a framework. The Google Maps API is used to get time and distances and as a front end in the online map section. MySQL is used as a database to store simulation data.The final result of this program is an assignment simulation application between driver and passenger using two algorithms and 3 factors, that is time, distance and last trip by the driver. Simulation can display a comparison of the results of the assignment to facilitate the process of comparison of algorithms.